Physical Fitness Management Of Madrasah Ibtidaiyah Students - Wening Nugraheni; Syahra Andriyany; Ahmad Alwi Nurudin (Journal Management of Sport, 2024)
This study was conducted with the aim of assessing the level of physical fitness of MI Muhammadiyah Cipetir students. The type of research used is descriptive quantitative, and the method applied is survey. The population that became the focus of the research was all MI Muhammadiyah Cipetir students. The research sample consisted of 267 students, selected through the total sampling method. Data collection techniques were carried out through TKJI tests and measurements, including sit-ups, vertical jump, pull-ups, 40 meter sprints, and 600 meter runs. Data analysis used a percentage-based quantitative descriptive statistical approach. The results showed that students' physical fitness level could be categorized as "Excellent" in 2 students (0.75%), "Good" in 68 students (25.47%), "Moderate" in 117 students (43.82%), "Less" in 70 students (26.22%), and "Very Poor" in 10 students (3.75%). Thus, it can be concluded that the level of physical fitness of MI Muhammadiyah Cipetir students in general is in the "Moderate" category.